The Accuracy of Patient Identification to Improve Understanding and Implementation of Patient Safety Principles in Health Care Facilities at Meilia Vocational High School Cinere Depok - Febriani, Nelly; Khairini, Hafizah; Azhari, Nurdinda; Arafah, Nathaniela; Ardiansari, Putri; Khairunnisa, Cintia Zahwa; Kusumadewi, Jovita Putri; Islam, Difa' Shohwatul; Annastasya, Dara; Pebriani, Putri Wiwit; Sulistiawati, Ratna; Nugroho, Regina Aprillia; Triana, Puput Adi (Yayasan Daarul Huda Kruengmane, 2025)
Patient safety is a fundamental aspect of healthcare that focuses on preventing avoidable injuries during the treatment process. One of the key elements in implementing patient safety is accurate identification, which serves to ensure that every medical and nursing action is given to the right patient. Although it has been regulated through Minister of Health Regulation No. 11 of 2017 and is a global priority according to the WHO (2023), many identification errors are still found due to low understanding and compliance with standard procedures. This community service activity aims to increase the understanding of Meilia Medika Cinere Vocational School students in Depok regarding the accuracy of patient identification through interactive education. The method used was a quantitative approach with a pre-post test one group design based on Project-Based Learning. The activity was carried out in October 2025 and involved 27 nursing students as participants. The education process was conducted through interactive lectures, discussions, simulations, and the use of visual media such as posters, videos, and PowerPoint presentations. The evaluation results showed an average increase in knowledge of 3.33%, from 95.56% in the pretest to 98.89% in the posttest. Although the increase was small because participants already had a high level of prior knowledge, this activity succeeded in strengthening awareness and positive attitudes toward the application of patient safety principles. As a result, interactive education based on visual media proved effective in strengthening understanding and instilling a culture of patient safety in nursing students at the vocational education level.